2017
DOI: 10.1371/journal.pone.0182970
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term dry immersion on bone remodeling markers, insulin and adipokines

Abstract: BackgroundDry immersion (DI), a ground-based model of microgravity previously used in Russia, has been recently implemented in France. The aim of this study was to analyze early events in a short-term DI model in which all conditions are met to investigate who is first challenged from osteo- or adipo-kines and to what extent they are associated to insulin-regulating hormones.MethodsTwelve healthy men were submitted to a 3-day DI. Fasting blood was collected during pre-immersion phase for the determination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 50 publications
4
31
0
Order By: Relevance
“…Any dissimilarity in the lists of significantly changed proteins could be explained by the differences in the dynamics of the development of effects in the ground-based experiments. The changes occurring during the dry immersion experiment develop rather quickly [9]—faster than during HDBR. Therefore, on the 21st day of the experiments, the physiological systems of the organism are in different states.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Any dissimilarity in the lists of significantly changed proteins could be explained by the differences in the dynamics of the development of effects in the ground-based experiments. The changes occurring during the dry immersion experiment develop rather quickly [9]—faster than during HDBR. Therefore, on the 21st day of the experiments, the physiological systems of the organism are in different states.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are certain ethical restrictions that allow only experiments with physical inactivity and diet modification, in particular, modification of the composition of basic nutrients, as well as exercise tests. Some experiments were specifically designed to simulate physiological changes under the influence of separate factors of spaceflight such as head-down bed rest, dry immersion, and isolation in sealed chambers [8,9]. Head down bed rest (HDBR) is one of the experimental models that limits the mobility of a person to strict bed rest, while the head of the bed is lowered relative to the horizontal axis [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, such conflicting results may be ascribed to measurement bias in humans. In this context, interesting data were reported by Linossier et al who assessed the effect of the acute increase in bone resorption on glucose metabolism in 12 healthy men exposed to microgravity (35). Authors observed that the onset of insulin-resistance was in response to increased bone resorption and concomitant to the increase of uOC (35).…”
Section: Osteocalcinmentioning
confidence: 91%
“…There were no effects of 7-day DI on bone formation or increase of bone resorption in the study of Kopp (2008). A recent study performed during 3-day DI, however, revealed significant decrement of bone formation markers, namely total procollagen type I N- and C-terminal propetides and osteoprotegerin (Linossier et al, 2017).…”
Section: Effects On Skeletal Systemmentioning
confidence: 95%